Hydrotherapy and cardiovascular rehabilitation: a new approach on late post-operative recovery after bariatric surgery - Piedade Vasconcellos Silva, Tiago José; Cunali Queiroz Telles, Gabriel; Okano Gimenes, Rafaela; Trimer, Renata (O Mundo da Saúde, 2006)
Obesity is defined as a pathology that affects patients presenting a body mass index greater that 30 kg/m. Epidemiological studies demonstrate that it is associated with the increase of the rate of cardiovascular illnesses, thus diminishing these patients’ life expectancy. The gastroplasty with Roux-en-Y sections the stomach for delimiting a reservoir of approximately 30 ml. To present hydro- therapy and cardiovascular rehabilitation as resources for late post-operative recovery of a patient submitted to bariatric surgery in order to verify if there are alterations in her functional capacity and quality of life. A patient 44 years old, feminine sex, submitted to two weekly sessions of hydrotherapy and three of ground physiotherapy for a period of 4 months. As evaluation instruments the test of 6 minutes walk and the SF-36 questionnaire of quality of life had been used. In the TC6 ‘, there had been an increase of 90 meters in the covered distance, and in the SF-36 improvement in the punctuation of 6 from 8 evaluated items. There had been an improvement in the quality of life and the functional capacity of the studied patient.